A medical teacher's manual for success five simple steps - Shields, Helen M. (Johns Hopkins University Press, 2011)
In this book the author shares methods for developing, implementing, and evaluating curricula for medical students employing five steps for use with any assignment. She discusses why and how to become a successful teacher, the personal qualities of these teachers, succeeding as a medical educator, and skills for assessment, feedback, writing evaluations and recommendations, and preclinical, clinical, postgraduate, and other teaching.